FACTORS THAT INFLUENCE A PERSON'S DECISION TO CONVERT ISLAM IN INDONESIA - Hafidza, Nurul; Naldo, Jufri (FORUM PAEDAGOGIK, 2025)
This study aims to identify and analyze the factors that influence an individual's decision to convert to Islam in Indonesia. As the country with the largest Muslim population in the world, Indonesia provides a unique context for understanding the dynamics of religious conversion, particularly to Islam. This research employs a qualitative approach using in-depth interviews with converts (converts) from diverse social, economic, and cultural backgrounds. The findings reveal four main factors that influence the decision to embrace Islam: (1) spiritual factors and the search for life's meaning, (2) the influence of the social environment, such as friends, spouses, or family, (3) attraction to Islamic teachings perceived as logical and calming, and (4) personal experiences or life events that serve as spiritual turning points. This study contributes to the field of the sociology of religion and can serve as a reference for Islamic outreach organizations and religious institutions in designing humanistic and context-sensitive approaches to da'wah.